PELAKSANAAN PROGRAM PEMBINAAN DAN PENGAWASAN INDUSTRI KECIL MENENGAH (IKM) OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU TAHUN 2012-2013 - Fasdani, Aidil Ulya; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study to determine why the program guidance and supervision iscarried out by the department of industry and trade city of Pekanbaru to the smalland medium industries and to identify obstacles in the process of coaching andsupervision are done. The method used is a qualitative method of data descriptiveassessment. Object of this study is the Department of Industry and Trade ofPekanbaru. The technique of collecting data using interviews, observation anddocumentation. By using key informants as a source of information which amounts to8 people. Based on the research that has been conducted based on the concept andtheory researchers found that program implementation guidance and supervision ofsmall and medium industries in Pekanbaru City conducted by the Department ofIndustry and Trade is not optimal.Keywords : Program, guidance and supervision, small and medium industries.